Visual transcriptions as socio-technical assemblages. (May 2021) - Aarsand, Pål; Sparrman, Anna
With the development of visual digital technologies it has become more common in the social sciences to both use and present research visually. This article explores different strategies for working with and including images in ethnomethodology and conversation analysis (EMCA) transcriptions. The purpose is to investigate how, and if, the ontology of the transcript changes when verbal transcripts become visual transcripts. The article explores what ensures that a transcript is still a transcript and what happens to the reflexive interpretative strategy fundamental to EMCA when new digital technologies make it possible to incorporate images in transcripts. The article's focus is on the social life of methods as well as methodological productivity showing how images can enact different social 'realities' and scientific knowledge.